1995
DOI: 10.1113/expphysiol.1995.sp003883
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates cationic amino acid transport activity in the isolated perfused rat pancreas

Abstract: SUMMARYThe effects of exogenous insulin, glucagon and streptozotocin-diabetes on influx (15 s) of L-lysine via a cationic amino acid transporter resembling system y+ were investigated in the isolated perfused rat pancreas. In non-diabetic pancreata, transport of L-lysine was saturable with an apparent Km of 2-11 + 0.29 mm and Vma_ of 2 21 + 0 20,mol min-' g-1 (n = 6). Bovine insulin (100 # u ml ') increased the maximal transport rate (Vmax = 349 + 030 /tmol min-' g-', n = 4, P < 0.05) for L-lysine 1 6-fold wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
(59 reference statements)
3
10
0
Order By: Relevance
“…Our results show that L-arginine transport occurs with relatively high affinity (K m 85 µM), is Na + -independent and inhibited by membrane depolarization, supporting previous reports showing that L-arginine transport in these cells is mediated primarily by the high-affinity membrane transporters hCAT-1 (K m ≈100-200 µM) or hCAT-2B (K m ≈200-400 µM) [3,10,39,45,50]. Insulin increases L-arginine transport in HUVEC [39,45] and activates Na + -independent L-lysine transport in rat pan- [29] and L-arginine transport in gastric mucosa [6]. Our results show that the insulin-mediated increase in Larginine transport was associated with a higher V max with no changes in the apparent K m .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results show that L-arginine transport occurs with relatively high affinity (K m 85 µM), is Na + -independent and inhibited by membrane depolarization, supporting previous reports showing that L-arginine transport in these cells is mediated primarily by the high-affinity membrane transporters hCAT-1 (K m ≈100-200 µM) or hCAT-2B (K m ≈200-400 µM) [3,10,39,45,50]. Insulin increases L-arginine transport in HUVEC [39,45] and activates Na + -independent L-lysine transport in rat pan- [29] and L-arginine transport in gastric mucosa [6]. Our results show that the insulin-mediated increase in Larginine transport was associated with a higher V max with no changes in the apparent K m .…”
Section: Discussionsupporting
confidence: 87%
“…Insulin increases the activity of system y + /CATs in HUVEC [45], rat pancreas [29], gastric mucosa [6] and CAT-1 expression in rat liver cells [49] and coronary myocytes [43]. However, there are no reports on the cell signalling mechanisms involved in the modulation of L-arginine transport and hCAT-1 and hCAT-2B expression in response to insulin in human endothelium [26,46].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, arginine uptake by normal rat RPE increased considerably due to the presence of insulin, high glucose concentrations or of insulin in combination with high glucose concentrations in the incubation medium. Although the mechanism of this increase is not understood, insulin is known to regulate a variety of amino acid transporters [28][29][30][31], and therefore glucose could indirectly raise the capacity of the arginine transporter.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin also enhances system y¤ activity in gastric glands (Contreras et al 1997), pancreas (Muñoz, Sweiry & Mann, 1995) and liver cells (Wu, Robinson, Kung & Hatzoglou, 1994). Other studies in umbilical vein endothelial cells have shown that both IGF_1 and insulin stimulate NO production via a Ca¥-independent mechanism (Tsukahara, Gordienko, Tonshoff, Gelato & Goligorsky, 1994).…”
Section: Discussionmentioning
confidence: 99%